The Development of Elderly Community Through Self Concept Enhancement in Achieveing Resilience in Taman Lansia Yogyakarta - Wahidah, Evita Yuliatul; Salim, Agus; Sirait, Sangkot; Kusumaputri, Erika Setyanti; Mustafidah, Nurmashani (Proceedings of Annual Conference on Community Engagement, 2022)
This Community Service is based on the implementation of social-based University Community Engagement (UCE) to connect education world with community. This coaching is designed using several methods, which are: the classical method by delivering content through a verbal approach with a variety of discussions in the room (indoor) as well as the game method and light simulation (outdoor). The result is identified as 60 participants were declared successful. It is proved that at the level of resilience there are 51 participants (85%) have very high resilience, and 9 participants (15%) have high level of resilience. The resilience items selected by the most patients are strongly agree, found in two characteristics, which are existential aloneness, 45 participants (75%), and meaningfulness characteristics, 48 participants (80%). The conclusion is social-based community service activities by developing the elderly community in Taman Lansia Yogyakarta through self-concept improvement program have significant impact on resilience.